Acoustic Cooperation: Acoustic Communication Regulates Conflict and Cooperation Within the Family - Mariette, Mylene M. (Frontiers in Ecology and Evolution, 2019)
Acoustic communication is central to many social interactions between family members. Whilst song and begging calls have been extensively studied, in this review, I focus on familial interactions where acoustic communication plays a critical role, but yet has often been overlooked. I show that considering acoustic information transfer challenges the traditional views on sexual and parent-offspring conflicts. In particular, I firstly discuss the role of acoustic communication between breeding partners in parental care negotiation and coordination. I consider the potential for vocalisations to signal partners’ state, in terms of current satiation or energy levels during parental care provisioning. Secondly, I review the occurrence of parent-embryo acoustic communication and highlight the possibility for acoustic developmental programming to facilitate the co-adaptation of offspring begging calls and parental provisioning capacities. I also discuss how acoustic information available to avian embryos from the environment may empower them to direct their development, independently of their parents. Thirdly, I bring together evidence on sib-sib acoustic communication before and after birth, and highlight its function in sibling cooperation for hatching synchronisation and resource partitioning. Overall, this synthesis demonstrates the importance of considering acoustic information to understand the evolution of parental care and cooperation.